Game of webs: species and web structure influence contest outcome in black widow spiders. (14th October 2019) - Jones, Cameron; Pollack, Lea; DiRienzo, Nicholas
Abstract: Population-level trait variation within species plays an often-overlooked role in interspecific interactions. In this study, we compared among-individual variation in web phenotype and foraging behavior between native black widows ( Latrodectus hesperus ) and invasive brown widows ( Latrodectus geometricus ). We staged repeated contests whereby native widows defended their webs against intruders of both species to 1) investigate how trait variation mediates web contest outcome among native widows and 2) see whether widow behavior differs in response to an invasive spider. In only one trait, the average number of foraging lines, did black widows differ from brown widows. Black widow residents that built more structural lines were more likely to successfully defend their webs from conspecific intruders (i.e., be the sole spider remaining on the web postinteraction). This association between web structure and contest outcome did not exist in trials between black widows and invasive brown widows; however, in interspecific interactions, these same residents were more likely to have intruders remain on the web rather than drive them away. Surprisingly, brown widows did not usurp black widows. Brown widows were never observed signaling, yet black widow residents signaled equally to intruders of both species. Our results suggest that among-individual variation among native species can influence the response toward invasive competitors and outcome of these interactions. Lay Summary: When native species compete with invasive animals, certain individuals may behave in a way that is inappropriate. In native black widows, females that construct webs with more defensive silk lines, relative to foraging silk lines, are better at defending their webs from conspecific intruders yet perform worse when defending against invasive brown widow intruders. Signaling toward web intruders safely resolves contests among natives but does nothing in contests with invasive widows.